Hyperforin Promotes Post-stroke Neuroangiogenesis via Astrocytic IL-6-Mediated Negative Immune Regulation in the Ischemic Brain - Yao, Hua; Zhang, Yujing; Shu, Huaqing; Xie, Bing; Tao, Yuanfa; Yuan, Yin; Shang, You; Yuan, Shiying; Zhang, Jiancheng (Frontiers in Cellular Neuroscience, 2019)
Hyperforin has been shown to be capable of promoting angiogenesis and functional recovery after ischemic stroke in our previous study. However, the exact mechanisms involved are not fully elucidated. In this study, adult male mice were subjected to 60-min transient middle cerebral artery occlusion followed by reperfusion for 28 days. Hyperforin was administrated to MCAO mice every 24 hours for 2 weeks starting at 14 days post-ischemia (dpi). Then flow cytometry, quantitative Real-time PCR (RT-qPCR), western blotting, immunohistochemistry, and functional assays were performed to explore the molecular mechanisms in vivo and in vitro. Our data showed that hyperforin increased astrocytic interleukin (IL)-6 in the ischemic hemisphere via TLR4 at 28dpi. The astrocytic IL-6 was essential to the promoting effects of hyperforin on the neural precursor cells (NPCs) proliferation, neuronal differentiation, angiogenesis and functional recovery after stroke. Furthermore, hyperforin promoted the infiltration of regulatory T cells (Tregs) to the ischemic hemisphere and increased Tregs-derived cytokine IL-10 and transforming growth factor-β (TGF-β) in a manner that was dependent on astrocytic IL-6. Astrocytic IL-6 was critical to the role of hyperforin in promoting the infiltration of T-helper (Th) type 2 cells to the ischemic hemisphere and Th2-derived cytokine IL-4, relative to Th1 and Th1-derived cytokine interferon-γ (IFN-γ), which decreased during stroke recovery. After depletion of CD25+ Tregs, the promoting effects of hyperforin on post-stroke neurogenesis was attenuated. Moreover, blockade of IL-4 and TGF-β abrogated the promoting role of hyperforin in post-stroke neurogenesis, angiogenesis and functional recovery. Our results reveal a previously uncharacterized role of astrocytic IL-6-mediated negative immune regulation in the promoting effects of hyperforin on post-stroke neurovascular regeneration and functional recovery.